Activray advance skeleton - Zakaria, Amir Imran; Mustapha, Haziq Hamadi; Affendi, Ahmad Mushtaqqim; Faaisal, Hazmi Nabil; Abdullah, Muhammad Firdaus; Azis, Siti Noraziana (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
According to the Department of Statistics Malaysia (DOSM), Mstar Portal reported when COVID-19 attack Malaysia since 2019-2020, Malaysia listed in 19 countries at risk of paralysis. This is because Malaysia facing the problem of a severe lack of oxygen supply due to the increase in covid 19 cases. They are stuck thinking about their own fate with paralysis disease not as they used to be like other normal people. On the other hand, they have difficulty to move their body muscle to do daily activities includes stand, sit and walk. It's unfortunate that they are unable to get out of bed and rely on others to handle everything towards them. At the same they also want to feel freedom like other normal people without having disabilities. Therefore “Activray Advance Skeleton” aims to help this paralysis people can feel like normal person that not having disabilities with using our product. Activray become most trending the new innovative product of back support belt. We use the technology system with having multiple features such button, voice and sound at back support belt, so our product can move the muscle of the person to go up using the technology we created especially our product is for paralysis people.